Analisis Pengujian Kebisingan dan Emisi Gas Buang pada Sepeda Motor Honda 110 cc Menggunakan Knalpot AHLM (Adaptive High-Performance, Low-Pollution Muffler) - Putra, Ni’mal Maula; Roziqin, Ahmad; Naryanto, Rizqi Fitri; Septiyanto, Angga; Maulana, Sonika; Rohman, Shohihatur (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The high levels of air pollution and noise from motor vehicles cause negative impacts on the environment and health. Innovation in exhaust systems is needed to address this issue. This study aims to analyze the effect of different exhaust types on noise levels and exhaust gas emissions in a Honda 110 cc motorcycle. The independent variable in this study is the type of exhaust (standard, free flow, and AHLM), while the dependent variables include noise level (dB) and emissions of carbon monoxide (CO) and hydrocarbons (HC). The control variables include measurement distance, engine operating temperature (80°C to 90°C), and fuel type (RON 90). The research method uses a quantitative experimental approach with a sound level meter to measure noise and a gas analyzer for exhaust emissions. Data analysis was performed using the Kruskal-Wallis test to determine differences among exhaust variations. The statistical test results showed no significant difference (p > 0.05) in noise levels and exhaust emissions among the three types of exhaust. However, descriptively, the AHLM muffler performed best, reducing noise by up to 5.88% compared to free flow, and decreasing CO emissions by 17% and HC by 1%. This study is limited to testing one type of motorcycle and laboratory conditions, so the results do not yet represent actual traffic conditions. Thus, the AHLM muffler has the potential to be an adaptive exhaust system innovation that is more environmentally friendly and effective in reducing noise and motor vehicle emissions.